PENGARUH KEPERCAYAAN MEREK, CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PENGGUNA JASA PADA PT. SICEPAT EKSPRES DENPASAR - Ni Made Sakha Dwi Ariesta; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (EMAS, 2022)
Consumer satisfaction with service company is defined as a situation where consumer expectations for a service are in accordance with received about the services that provide to consumers. This study aims to determine the effect of brand trust, brand image, and service quality on service user satisfaction at PT. Sicepat Express Denpasar. The population of this research is consumer have used the services of PT. Sicepat Express Denpasar, with samples determined based on the number of indicators multiplied by five. The sample used was 75 respondents. The analytical technique is used multiple linear regression analysis, classical assumption test, and appropriate model test. The results of this study showed that brand trust has a positif and significant effect on consumer satisfaction at PT. Sicepat Express Denpasar. Brand Image has a positive and significant effect on consumer satisfaction at PT. Sicepat Express Denpasar. Service quality has a positive and significant effect on consumer satisfaction at PT. Sicepat Express Denpasar.